Melatonin Reduces NLRP3 Inflammasome Activation by Increasing α7 nAChR-Mediated Autophagic Flux - Víctor Farré-Alins; Paloma Narros-Fernández; Alejandra Palomino-Antolín; Céline Decouty-Pérez; Ana Belen Lopez-Rodriguez; Esther Parada; Alicia Muñoz-Montero; Vanessa Gómez-Rangel; Francisco López-Muñoz; Eva Ramos; Águeda González-Rodríguez; Luis Gandía; et al. (MDPI AG, 2020)
Microglia controls the immune system response in the brain. Specifically, the activation and dysregulation of the NLRP3 inflammasome is responsible for the initiation of the inflammatory process through IL-1β and IL-18 release. In this work, we have focused on studying the effect of melatonin on the regulation of the NLRP3 inflammasome through α7 nicotinic receptor (nAChR) and its relationship with autophagy. For this purpose, we have used pharmacological and genetic approaches in lipopolysaccharide (LPS)-induced inflammation models in both in vitro and in vivo models. In the BV2 cell line, LPS inhibited autophagy, which increased NLRP3 protein levels. However, melatonin promoted an increase in the autophagic flux. Treatment of glial cultures from wild-type (WT) mice with LPS followed by extracellular adenosine triphosphate (ATP) produced the release of IL-1β, which was reversed by melatonin pretreatment. In cultures from α7 nAChR knock-out (KO) mice, melatonin did not reduce IL-1β release. Furthermore, melatonin decreased the expression of inflammasome components and reactive oxygen species (ROS) induced by LPS; co-incubation of melatonin with α-bungarotoxin (α-bgt) or luzindole abolished the anti-inflammatory and antioxidant effects. In vivo, melatonin reverted LPS-induced cognitive decline, reduced NLRP3 levels and promoted autophagic flux in the hippocampi of WT mice, whereas in α7 nAChR KO mice melatonin effect was not observed. These results suggest that melatonin may modulate the complex interplay between α7 nAChR and autophagy signaling.